Um estudo sobre a pressa: considerações a partir das noções de temporalidade na psicanálise - Costa, Robert Pessoa (2024)
The present work aims to analyze the notion of haste related to the psychoanalytic experience based on the understanding of temporalities present in Freud's work and in Lacan's teaching. Although the notion of haste does not have the status of a concept, the aim is to construct it theoretically, based on the clinical contributions indicated by the aforementioned authors. Lacan, resuming the temporal scheme of Freudian nachträglich, highlights the importance of time in the work of elaboration throughout an analysis and formulates the concept of logical time, including haste as a condition to reach conclusive moments in the treatment. The proposed research is a theoretical study and a bibliographical review on haste in this specific context of the theoretical-methodological framework of psychoanalysis. We start from Freudian matrices, especially those related to the concepts of trauma and repetition, to understand the basis on which Lacan defines the rush in logical time and its clinical incidence. We aim, therefore, to identify the notion of haste in the context of psychoanalysis and analyze its clinical and theoretical developments in these two authors to discuss, in addition, its contemporary relationship with social acceleration and the diagnostic furor of certain neurobiological approaches to psychological suffering. As a result, we can contextualize the notion of analytical haste and observe that it requires the necessary time to establish itself in opposition to current demands for immediate and accelerated responses. From this we conclude that this notion is an important ethical guideline for thinking about the subject's desire in the face of alienation by social control regimes and the contingencies of real.